Student perceptions of using DataCamp in a data wrangling course. (29th September 2022) - Anderson, Billie
This study presents the results of a professor's semester-long experience of teaching a data wrangling course to a Master of Business Administration (MBA) class where most students had little or no background in coding or computing. The goal of this study was to better understand students' perceptions using DataCamp to learn data wrangling concepts. Voluntary, self-reported data were collected at the end of learning modules throughout the semester to evaluate their learning experience using DataCamp to learn data wrangling concepts. One major finding of this study is that the majority of students were surprised at how long it took them to complete more real-world problems in RStudio, given their previous experience with DataCamp. This finding speaks to some of the limitations of DataCamp in delivering the rich, complex, data-centered experiences that students need. This finding suggests that more open-ended problem-solving assignments can push students beyond what they learn from DataCamp alone.